Parallel texts from Försäkringskassan - Dahlberg, Simon; Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Forms that have been downloaded from the website (forsakringskassan.se) plus with e-mail templates that were sent to us directly from Försäkringkassan by e-mail. All the files are in Swedish and at least one more language.

Blanketter som laddats ned från webbplatsen samt interna mejlmallar som skickats till oss direkt av Försäkringskassan. Allt finns på svenska och minst ett språk till.
Parallella texter från Försäkringskassan
Keywords: Social Security; Socialförsäkring; Universal Health Insurance; Allmän sjukförsäkring; welfare policy; social- och välfärdspolitik; Social welfare systems/structures; Sociala välfärdssystem/-strukturer; Public Administration Studies; Studier av offentlig förvaltning